FORECASTING OF SALES OF COMPUTER EQUIPMENT USING EXPONENTIAL SMOOTHING METHOD - Muhammad Iqbal Panjaitan (Sean Institute, 2019)
In the business world, it takes a prediction or estimate of an action that will be processed to follow up on the results that will be expected in the next few periods. Therefore, we need a forecasting process that is used to support the decisions of a company to get the maximum profit. Exponential Smoothing method is a method that has been widely used for forecasting because it has a pretty good performance. Exponential smoothing method is a procedure that continuously improves forecasting by averaging the past value of a time series data by decreasing (exponential). Exponential Smoothing method has several alpha parameters used, namely 0.1; 0.5; 0.9 to support the calculation that will be used in forecasting. With these methods, calculations can be done to find the best optimal value with the smallest error rate. The selected forecasting method is used to forecast computer sales.